1993
DOI: 10.1037/0735-7044.107.4.618
|View full text |Cite
|
Sign up to set email alerts
|

Severity of spatial learning impairment in aging: Development of a learning index for performance in the Morris water maze.

Abstract: The Morris water maze task was originally designed to assess the rat's ability to learn to navigate to a specific location in a relatively large spatial environment. This article describes new measures that provide information about the spatial distribution of the rat's search during both training and probe trial performance. The basic new measure optimizes the use of computer tracking to identify the rat's position with respect to the target location. This proximity measure was found to be highly sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

53
706
1
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 752 publications
(762 citation statements)
references
References 16 publications
(25 reference statements)
53
706
1
2
Order By: Relevance
“…In agreement with previous studies, the cumulative search error measure appeared to be most sensitive for detecting age-related differences (particularly at middle-age). However, pathlength may be the optimal and most conservative choice for such analyses in aged F344 rats due to the lack of confounds with swim speed [19]. Barnes et al (1997) reported that, early in training, when performance on individual training trials was plotted on a frequency histogram, both young and aged rats exhibited a strong bimodality in performance such that on some trials rats of both ages had short swim paths whereas on other trials they had long swim paths.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In agreement with previous studies, the cumulative search error measure appeared to be most sensitive for detecting age-related differences (particularly at middle-age). However, pathlength may be the optimal and most conservative choice for such analyses in aged F344 rats due to the lack of confounds with swim speed [19]. Barnes et al (1997) reported that, early in training, when performance on individual training trials was plotted on a frequency histogram, both young and aged rats exhibited a strong bimodality in performance such that on some trials rats of both ages had short swim paths whereas on other trials they had long swim paths.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate cumulative search error, the rat's distance from the platform was sampled 10 times/s and these distances were averaged into 1 s bins. Cumulative search error is the sum of these 1 s bins minus the optimal path from the start location to the platform [19]. Additional measures of performance (e.g., latency, swim speed) also were recorded.…”
Section: Spatial Reference Memory Task-trainingmentioning
confidence: 99%
See 3 more Smart Citations